(Mis)trusted Contact: Resettlement Knowledge Assets and the Third Space of Refugee Reception - Kyriakides, Christopher; McLuhan, Arthur; Anderson, Karen; Bajjali, Lubna; Elgendy, Noheir (Refuge)

(untitled) (Centre for Refugee Studies, York University, 2019)
Drawing on interviews with 204 participants in two studies of privately sponsored refugee resettlement in Ontario, Canada, we explore the resettlement effects of pre-arrival contact on the interactional dynamics between private sponsors and privately sponsored Syrian refugees. Those who had regular pre-arrival contact via digital applications such as Facebook, Skype, and Whatsapp reported more positive, “successful” resettlement experiences than those who had not. This pre-arrival interactive dynamic has theoretical/conceptual implications beyond an understanding of the benefits of “information exchange.” Pre-arrival sponsor-sponsored interaction is not bound by the contexts of displacement or resettlement, but constitutes a “third space” of reception, co-created through trusted contact. We develop the concept of “resettlement knowledge assets” and report on how these assets emerge through pre-arrival trust building, modify the resettlement expectations of both sponsors and sponsored, and reduce resettlement uncertainty.